2022
DOI: 10.1111/een.13160
|View full text |Cite
|
Sign up to set email alerts
|

Microbial volatiles and succession of beetles on small carrion

Abstract: Ecological succession is understood in general terms (facilitation, tolerance, inhibition) even though the system‐specific mechanisms often remain elusive. The succession of insects on carrion is an important model because of its applications to ecosystem function and forensic science. It recently has been hypothesized that changing volatile cues produced by microbes drive succession on carrion. The authors investigated how two blends of sulphur volatiles attracted beetles that typically colonise during the fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…This discovery is intriguing, as multiple studies have demonstrated the use and prevalence of DMTS over DMDS for navigation and oviposition in other species, such as carrion-eating flies like Lucilia sericata and Calliphora vicina . Furthermore, electroantennogram studies indicated strong responses to DMTS but limited to no response to DMDS 51,52 . Given that there are no reports of Dbus being captured from carrion or carrion-mimicking flowers, it is reasonable to hypothesize that this shift in ligand preference between these two structurally related oligosulfides could be a contributing factor in the discrimination of food and oviposition sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This discovery is intriguing, as multiple studies have demonstrated the use and prevalence of DMTS over DMDS for navigation and oviposition in other species, such as carrion-eating flies like Lucilia sericata and Calliphora vicina . Furthermore, electroantennogram studies indicated strong responses to DMTS but limited to no response to DMDS 51,52 . Given that there are no reports of Dbus being captured from carrion or carrion-mimicking flowers, it is reasonable to hypothesize that this shift in ligand preference between these two structurally related oligosulfides could be a contributing factor in the discrimination of food and oviposition sites.…”
Section: Discussionmentioning
confidence: 99%
“…The use of short-chain oligosulfides as semiochemicals by insects has been documented in other contexts, involving mosquitoes, bed bugs, blow flies, parasitic wasps, cabbage root flies, and carrion-mimicking flower breeding flies [46][47][48][49][50] . Decaying carrion and carrion-mimicking flowers have been found to emit significant amounts of both DMDS and DMTS in their bouquets 47,50,51 .…”
Section: Ecology and Host Preferencementioning
confidence: 99%
“…Recently, methyl thiocyanate has been identified as an important attractant (Trumbo & Steiger, 2020 ). Moreover, the synergy, emission rates (volatility), and relative concentrations of multiple compounds are important as well (Podskalská et al., 2009 ; Trumbo & Dicapua, 2021 ; Trumbo & Newton, 2022 ). Therefore, to elucidate the comprehensive mechanisms that attract carrion insects to carcasses, dose–response tests and experiments considering relative concentrations of various volatile organic compounds are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have elucidated the mechanisms of carrion insect succession from a microscopic perspective. These studies have demonstrated temporal changes in carrion insects corresponding to changes in volatile organic compounds emitted from carcasses (Recinos‐Aguilar et al., 2020 ; Trumbo & Newton, 2022 ). This idea is called the gas‐emanation hypothesis (Nadeau et al., 2015 ), and carrion insect succession is thought to be driven by the temporal change in volatile organic compounds perceived by different insects (Dekeirsschieter et al., 2009 , 2012 ; Forbes et al., 2014 ; Kasper et al., 2012 ; Stadler et al., 2013 ) resulting from microbial succession on carcasses (Pechal, Crippen, et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%